The present work deals with the development of polystyrene (PS) nanocomposites through solvent blending technique with diverse contents of modified CoeAl layered double hydroxide (LDH). The prepared PS as well as PS/CoeAl LDH (1e7 wt.%) nanocomposites were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), rheo-logical analysis, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The XRD results suggested the formation of exfoliated structure, while TEM images clearly indicated the inter-calated morphology of PS nanocomposites at higher loading. The presence of various functional groups in the CoeAl LDH and PS/CoeAl LDH nanocomposites was verified by FTIR analysis. TGA data confirmed that the thermal stability of PS composites was enhanced significantly as compared to pristine PS. While considering 15% weight loss as a reference point, it was found that the thermal degradation (Td) tem-perature increased up to 28.5 C for PS nanocomposites prepared with 7 wt.% CoeAl LDH loading over pristine PS. All the nanocomposite samples displayed superior glass transition temperature (Tg), in which PS nanocomposites containing 7 wt.% LDH showed about 5.5 C higher Tgover pristine PS. In addition, the kinetics for thermal degradation of the composites was studied using Coats-Redfern method. The Criado method was ultimately used to evaluate the decomposition reaction mechanism of the nano-composites. The complex viscosity and rheological muduli of nanocomposites were found to be higher than that of pristine PS when the frequency increased from 0.01 to 100 s 1 - Nguyen, Tien Thao (ĐHQGHN, 2017)
p. 337-342